The Erosion of Tabayyun: Cancel Culture, Public Shaming, and the Crisis of Islamic Digital Literacy - Naad, Darul; Cut Syamsidar; Rubino (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The rise of cancel culture on social media presents a critical challenge to Islamic digital literacy, particularly concerning the ethical principles of communication. This study investigates the erosion of the tabayyun (verification) principle amidst the normalization of public shaming, using the cancel culture phenomenon surrounding Indonesian public figure Gofar Hilman as a case study. Employing a digital netnography approach and thematic analysis, this research examines netizens' discourse, social media interactions, and digital public opinion mobilizations. The findings reveal that digital communities often bypass the verification process (tabayyun) and the ethical mandate of concealing others' faults (satr al-ʿayb), favoring instant moral judgment and collective delegitimization. While cancel culture operates as a modern mechanism for public accountability, it frequently mutates into digital vigilantism that contradicts Islamic communication ethics. This study contributes to the contemporary discourse on digital religion by providing a theoretical framework that bridges social media phenomena with Islamic ethical norms. Ultimately, the research emphasizes the urgent need to revitalize Islamic digital literacy to navigate the complexities of digital public spheres responsibly.